Kinetics and mechanism of tertiary amine-catalyzed cleavage of N `-morpholino-N-(2 `-methoxyphenyl)phthalamide: Kinetic evidence for the presence of a reactive intermediate on the reaction path - Sim, Yoke-Leng.; Khan, M.N. (John Wiley & Sons, 2010)
Pseudo-first-order rate constants (k(obs)) for tertiary amine (DABCO and Me(3)N) buffer-catalyzed cyclization of N'-morpholino-N-(2'-methoxyphenyl)phthalamide (1) to N-(2'-methoxyphenyl)phthalimide (2) reveal saturation (nonlinear) plots of k(obs) versus vertical bar Buf vertical bar(T) (total tertiary amine buffer concentration) at a constant pH. Such plots at different pH have been attributed to the presence of a reactive intermediate (T(-)) formed by tertiary amine buffer-catalyzed intramolecular nucleophilic addition of the secondary amide nitrogen to the carbonyl carbon of the tertiary amide group of 1. (C) 2010 Wiley Periodicals. Inc. Int J Chem Kinet 42: 263-272, 2010